2010
DOI: 10.1172/jci43426
|View full text |Cite
|
Sign up to set email alerts
|

Labeled lines meet and talk: population coding of somatic sensations

Abstract: The somatic sensory system responds to stimuli of distinct modalities, including touch, pain, itch, and temperature sensitivity. In the past century, great progress has been made in understanding the coding of these sensory modalities. From this work, two major features have emerged. First, there are specific neuronal circuits or labeled lines transmitting specific sensory information from the skin to the brain. Second, the generation of specific sensations often involves crosstalk among distinct labeled lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
125
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(136 citation statements)
references
References 107 publications
7
125
3
1
Order By: Relevance
“…This evidence for cross‐modal interaction and convergence at the spinal level is incompatible with the classic specificity theory (ie, of labeled lines), and is driving a paradigm shift in the way somatosensation is currently viewed. The emerging “population coding model” suggests that temperature and pain perception arises from the joint activity across several neuronal populations, rather than depending on neural signals of specific labeled lines, with 1 dominant line associated with each specific sensory quality 39, 40, 41, 42. Our experiments are consistent with the view that TGI perception is largely influenced by the pooled activity of spinal neurons within 1 or 2 spinal segments.…”
Section: Discussionsupporting
confidence: 87%
“…This evidence for cross‐modal interaction and convergence at the spinal level is incompatible with the classic specificity theory (ie, of labeled lines), and is driving a paradigm shift in the way somatosensation is currently viewed. The emerging “population coding model” suggests that temperature and pain perception arises from the joint activity across several neuronal populations, rather than depending on neural signals of specific labeled lines, with 1 dominant line associated with each specific sensory quality 39, 40, 41, 42. Our experiments are consistent with the view that TGI perception is largely influenced by the pooled activity of spinal neurons within 1 or 2 spinal segments.…”
Section: Discussionsupporting
confidence: 87%
“…Subsequent genetic and pharmacological approaches were applied to confirm that STAT3 indeed positively regulates the expression of LDHB at transcriptional level. 5 Taking into account that STAT3 is a known downstream effector of mTORC1, 10 our data suggest that activated mTORC1 signaling upregulates LDHB through activation of STAT3 (Fig. 1).…”
mentioning
confidence: 72%
“…Because c-Maf knock-out mice die within a few hours after birth, it will be of interest to generate c-Maf conditionally deficient mice and investigate whether the somatosensation is affected when c-Maf is deleted in the dorsal horn. Studies in the past century have suggested that the perception of specific sensory modalities might be best explained by the population-coding (also called selectivity) hypothesis (Ma, 2010). One important step in sensory biology is to better delineate the neuronal subtypes within the dorsal horn and characterize their physiological functions (Basbaum et …”
Section: Transcriptional Control Of Development Of Dorsal Horn Neuronsmentioning
confidence: 99%